Scalp and Skull Reconstruction in Patients Irradiated for Tinea Capitis in Childhood: The Scalp Exchange Procedure - Fliss, Ehud; Zaretski, Arik; Maoz-Halevy, Eyal D.; Gur, Eyal; Yanko, Ravit (Journal of Reconstructive Microsurgery Open, 2020)
Background Approximately 70,000 Israelis underwent scalp irradiation for tinea capitis infection during their childhood, as did many other children worldwide. Long-term follow-up data showed that these children had an increased risk of aggressive and multiple nonmelanoma skin cancers, meningiomas, and other malignancies. Resection of these lesions creates a defect of soft tissue, bone, and dura, and requires scalp and skull reconstruction with local or free flaps in the irradiated field.Methods Sixteen patients with a history of childhood scalp irradiation underwent scalp and skull reconstruction in our department (2000–2018). Data on demographics, oncological status, operative details, and postoperative outcome were retrospectively collected and analyzed.Results The study group included 11 males and 5 females (average age at surgery, 70 years). The most common lesions were meningiomas (n = 9) and basal cell carcinomas (n = 8), and the most common indication for reconstruction was chronic exposure of deep structures (skull, dura, brain tissue, and titanium mesh; n = 9). Thirteen patients underwent primary free flap reconstruction and three underwent primary local flap reconstruction. Flap failure requiring reoperation occurred in one patient of the free flap reconstruction group (7%) and in all three patients of the local flap reconstruction group.Conclusion Long-term consequences of childhood depilatory treatments of the scalp by irradiation are now surfacing. Our experience showed that in such cases, surgeons should aim for a more aggressive approach with wide resection and primary free flap reconstruction, and that favorable long-term functional and aesthetic results can safely be achieved using this reconstruction approach.
Keywords: microsurgery; scalp reconstruction; scalp irradiation